A Case Series of Congenital Pouch Colon- A Rare Regional Variant of Covered Bladder Exstrophy - Chadha, Rajiv; M, Aditya; Khan, Niyaz Ahmed; Yadav, Partap Singh; Gupta, Amit; Roy Choudhury, Subhasis (Iranian Journal of Pediatric Surgery, 2025)
Introduction: The clinical, radiologic and cystourethroscopic (CUS) findings regarding the colonic pouch, its terminal colovesical fistula (CVF) and lower urinary tract (LUT) in 27 boys with congenital pouch colon (CPC) and associated anorectal malformation (ARM) are described and discussed. Material and Methods: Records of 27 boys with CPC in whom radiologic studies and/ or CUS yielded information about the colonic pouch, CVF, and the LUT were studied. Relevant clinical findings were recorded. Results: CPC subtypes were Type I (n=1); Type II (n=13); Type III (n=1), and Type IV (n=12). Five patients (18.5%) had hypospadias and 3 (11.1%) unilateral undescended testis. X-Rays spine (n=25) showed normal sacrum (n=21) and partial sacral agenesis (n=4). Ultrasound (n=27) showed normal kidneys (n=21), unilateral malrotated kidney (n=1), unilateral hydronephrosis (n=2), and hydroureteronephrosis (n=3). Micturating cystourethrogram (n=12) showed a large, lobulated, smooth-walled urinary bladder (n=7) and vesicoureteral reflux (n=6). Contrast study of the colonic pouch (n=16) showed the pouch ending in a long wide CVF opening at the bladder neck with, in 11 patients (68.75%), filling of a large, lobulated urinary bladder. CUS (n=22) showed a competent bladder neck and an abnormal verumontanum pulled-up into the bladder neck. In 16 patients, the CVF opened in the trigone, just cranial to the right (n=13) or left (n=3) of the verumontanum. Conclusion: CPC likely results from an early, ‘localized’ error in cloacal septation by the uro-rectal septum with faulty development of adjacent developing structures. The long-term clinical consequences on bladder dynamics and male fertility need attention.